Narratives of Senior Social Entrepreneurship in the Silver Economy - Andrzej, Klimczuk (Magyar Gerontológia, 2023)
The basic assumption of the paper is the recognition that the complexity of the challenges related to population ageing forces the development of cooperative links in the area of the silver economy between public policy entities representing various sectors. In other words, there is a need for more intensive and better-coordinated cooperation between organisations in the commercial sector, public sector, non-governmental sector, informal sector and social economy sector (e.g., cooperatives).